Dependability Characteristics - Indicators for Maintenance Performance Measurement of Manufacturing Technology - Teringl, Adam; Aleš, Zdeněk; Legát, Václav (Manufacturing Technology Journal, 2015)
Authors define general dependability characteristics (reliability, maintainability, supportability and availability) and their measures. Further there is introduced method of data collection which shall be planned taking into account appropriate targets. Dependability data analysis needs clear understanding of an object, its operation, environment and physical attributes to be obtained required dependability measures which are described. These measures can be used as indicators for measuring maintenance impacts on reliability and maintainability. Data collection and its evaluation help to monitor the impact of maintenance on these indicators. Dependency between non-fulfillment of preventive maintenance and failure intensity including maintenance costs are also evaluated.
Keywords: Maintenance; Reliability; Availability; Preventive maintenance; Fulfillment of maintenance